A three-electrode multi-module sensor for accurate bodily-kinesthetic monitoring. (February 2020) - Wang, Haobin; Song, Yu; Guo, Hang; Wan, Ji; Miao, Liming; Xu, Chen; Ren, Zhongyang; Chen, Xuexian; Zhang, Haixia
Abstract: In response to the ongoing challenges for health care and human motion monitoring, this work proposes a three-electrode multi-module sensor (TEMS) integrating proximity feedback, compression sensing and stretching perception. With the assist of the porous carbon nanotubes (CNTs)-polydimethylsiloxane (PDMS) patch in optimized parameters, the unification of the device's out-of-plane non-contact sensing and in-plane contact segmental detection is realized. Besides, coordinated with a set of symmetrically patterned Ag nanowires (NWs) electrodes with specified initial conductivity, the device is highly-sensitive to two-dimensional strains and qualified for recognizing the horizontal tension strain as small as 0.077% and the vertical pressure exerted by a piece of scrip (0.18 Pa) in fast response (millisecond level). The anti-interference ability of the signals is ensured by the PDMS encapsulation and regional stiffness of the device. Furthermore, the simplified fabrication process based on PDMS doping/modification is suitable for human skin-attachable applications, especially as the accurate differentiation of similar motions and the time-phased judgment of continuous movements through collaboration among acquisition results. Graphical abstract: Smart healthcare electronics have vastly propelled the development of real-time field monitoring physiological signals and movement information with better comfort and portability. Faced with challenges of the richness and accuracy of acquired data to be further improved, we propose a multi-functional three-electrode sensor integrates the ability of electrostatic proximity detection and two-dimensional resistive-type strain sensing, which is promising for precisely bodily-kinesthetic monitoring.(a) Structural schematic of the device. (b) Distinct signals generated from different body motions by the three modules. (c) Application scenarios of time-phased judgments of continuous combined motions. Image 1 Highlights: Such sensor integrating proximity feedback, compression sensing and stretching perception with anti-interference ability. Utilizing porous CNT-PDMS patch, the out-of-plane non-contact sensing and in-plane contact detection are unified. Coordinated with patterned Ag NWs film, the device is qualified for recognizing the 0.077% strain and 0.18 Pa pressure. Exploiting PDMS doping/modification processes are suitable for human skin-attachable motion monitoring.